2016
DOI: 10.3390/computation4040038
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Anderson Accelerated Coupling of Lattice Boltzmann and Navier–Stokes Solvers

Abstract: Abstract:We present an Anderson acceleration-based approach to spatially couple three-dimensional Lattice Boltzmann and Navier-Stokes (LBNS) flow simulations. This allows to locally exploit the computational features of both fluid flow solver approaches to the fullest extent and yields enhanced control to match the LB and NS degrees of freedom within the LBNS overlap layer. Designed for parallel Schwarz coupling, the Anderson acceleration allows for the simultaneous execution of both Lattice Boltzmann and Navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The AA algorithm has been widely used in many fields due to its ease of application, fast convergence, good performance in high-dimensional environments, and large computational savings. These application areas include plasma physics (Willert et al, 2014), nonlinear radiation diffusion equations (An et al, 2017), flow problems (Atanasov et al, 2016), geometry (Brezinski et al, 2018), computer graphics (Ouyang et al, 2020), wave propagation (Yang et al, 2020(Yang et al, , 2021, robot localization (Pavlov et al, 2018), K-means clustering (Zhang et al, 2018), computer vision (Scieur et al, 2018, and reinforcement learning (Geist and Scherrer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The AA algorithm has been widely used in many fields due to its ease of application, fast convergence, good performance in high-dimensional environments, and large computational savings. These application areas include plasma physics (Willert et al, 2014), nonlinear radiation diffusion equations (An et al, 2017), flow problems (Atanasov et al, 2016), geometry (Brezinski et al, 2018), computer graphics (Ouyang et al, 2020), wave propagation (Yang et al, 2020(Yang et al, , 2021, robot localization (Pavlov et al, 2018), K-means clustering (Zhang et al, 2018), computer vision (Scieur et al, 2018, and reinforcement learning (Geist and Scherrer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They include analysis and design optimization of a variety of Stokes flows through capillaries, porous media flows, heat transfer problems under stationary conditions, and since the LB methods are explicit marching in nature, efficient solution techniques need to devised to accelerate their convergence (see e.g. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]). A recent review of the literature in the LB approach for such problems can be found in [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…However, in conventional computational code, it would still be difficult to take the filtration process into consideration, because we must set the complex boundary conditions at the very concave and convex filter substrate. Quite recently, a lattice Boltzmann method (LBM) has been widely used for alternative fluid simulation [7][8][9][10][11][12][13]. Many research papers have been published, especially for simulations in porous media [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%